PENGARUH VIRGIN COCONUT OIL (VCO) DI DALAM BASIS KRIM TERHADAP PENETRASI ZAT AKTIF - Henny Lucida; Vinny Hosiana; Vivi Muharmi (Jurnal Ilmiah Farmasi, 2007)
ABSTRACTA study on formulation of cream in a base containing Virgin Coconut Oil (VCO) withPiroxicam (1%) as a model has been undertaken. VCO concentration in the cream-base weremade 0 %, 31%, 36% and 41% respectively to determine the influence of VCO concentration on thepenetration profile of the drug. The profil of penetration was determined by using Franz diffusioncell (vertical type) with the mice’s skin and pH 8 phosphate buffer as membrane and mediumrespectively. Concentration of piroxicam released was determined spectrophotometically atwavelength 353.2 nm. Results indicated that the penetration profile of piroxicam from formula 1, 2and 3 followed zero order kinetic with the slope (k) of 0.0171 (r = 0.9913); 0.0217 (r = 0.9869) and0.0217 (r = 0.9939) respectively, while that from formula 4 followed Higuchi equation with the slope(k) of 0,0570 mg/sec2 / 1(r = 0.9853). The highest rate was observed from Formula 4 (VCOconcentration was 41%). Statistical análysis showed that VCO affected the release of piroxicamfrom the formulation significantly (p